Persuasion in Public Discourse : Cognitive and Functional Perspectives - Jana Pelclová; Wei-lun Lu (John Benjamins Publishing Company, 2018)
This book approaches persuasion in public discourse as a rhetorical phenomenon that enables the persuader to appeal to the addressee's intellectual and emotional capacities in a competing public environment. The aim is to investigate persuasive strategies from the overlapping perspectives of cognitive and functional linguistics. Both qualitative and quantitative analyses of authentic data (including English, Czech, Spanish, Slovene, Russian, and Hungarian) are grounded in the frameworks of functional grammar, facework and rapport management, classical rhetoric studies and multimodal discourse analysis and are linked to the constructs of (re)framing, conceptual metaphor and blending, mental space and viewpoint. In addition to traditional genres such as political speeches, news reporting, and advertising, the book also studies texts that examine book reviews, medieval medical recipes, public complaints or anonymous viral videos. Apart from discourse analysts, pragmaticians and cognitive linguists, this book will appeal to cognitive musicologists, semioticians, historical linguists and scholars of related disciplines.